2003
DOI: 10.1155/2003/857869
|View full text |Cite
|
Sign up to set email alerts
|

Ursodeoxycholic Acid and Atorvastatin in the Treatment of Nonalcoholic Steatohepatitis

Abstract: The use of atorvastatin in NASH patients with hyperlipidemia was found to be both effective and safe. The benefit of statin and UDCA therapy in normolipidemic patients with NASH requires confirmation with further placebo-controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
12

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(126 citation statements)
references
References 12 publications
4
110
0
12
Order By: Relevance
“…Severe liver damage and liver failure are very rare (119). Paradoxically, statins are currently used to treat NAFLD (120,121), and recent studies suggest that statins are hepatoprotective in patients with HCV (122).…”
Section: Pharmacologic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Severe liver damage and liver failure are very rare (119). Paradoxically, statins are currently used to treat NAFLD (120,121), and recent studies suggest that statins are hepatoprotective in patients with HCV (122).…”
Section: Pharmacologic Therapymentioning
confidence: 99%
“…While many studies have shown improvement in steatosis, there are neither long-term studies to determine whether they alter the natural history of the disease nor studies to indicate whether relapse occurs after treatment withdrawal. Gemfibrozil (145), vitamin E (146), metformin (88 -91), betaine (147), pioglitazone (92)(93)(94)(95)(96), rosiglitazone (97), atorvastatin (120,121), losartan (128), orlistat (148), and pentoxifylline (149) have all been tried and have all been shown in small trials to improve liver enzymes. Modest histologic improvement over 6 -12 months is seen with some of the agents.…”
Section: Treatment Of Nafldmentioning
confidence: 99%
“…Kiyici et al (16) carried out a study evaluating atorvastatin in patients with NASH, and observed a significant reduction in the aminotransferases levels. In ammatory activity…”
Section: Nash As Well As May Test the Results Of Several Drugs In Itsmentioning
confidence: 99%
“…To date, atorvastatin, pravastatin, and rosuvastatin have been studied. An important point about these studies is that the statin doses were not equipotent nor comparable in their lipid lowering effect [64] .…”
Section: Statinsmentioning
confidence: 99%